A NON-STANDARD REBELLION OF THE FREE SPIRIT IN THE WORK OF RAUF PARFI (Scientific journal of the Fergana State University, 2023)
The article gives a brief overview of the work of the poet Rauf Parfi and analyzes his sonnets and hokku. the attitude of the representatives of Uzbek and foreign literature to the works of Rauf Parfi was analyzed, and in the process of analysis the formal semantic features of the poems were revealed through the examples of sonnets and hokku. The title of the "trinity" in the works of the poet Rauf Parfi refers to a type of poem called hokku. in hokku the human mood is reflected through nature and nature. this article describes the concept of the sonnet and the poet’s thoughts on it. the sonnet, along with beautiful examples of metaphor, subtly expresses the wonderful waves of the poet's psyche. This article looks at the work of world literature, compares it with the work of Rauf Parfi, and explores the peculiarities and differences in his creative work.